Mechanics of Mindfulness: Investigating Metacognitive Beliefs as a Pathway of Effect on Anxiety and Depression - Corey Jackson; Christian M. Jones (European Journal of Investigation in Health, Psychology and Education)
This study aimed to address the dearth of literature on mechanisms of effect of mindfulness-based interventions by investigating metacognitive beliefs as a potential mechanism of symptomology-reduction effects. The Cognitive Attentional Syndrome (CAS) component of the Self-Regulatory Executive Function (S-REF) model was augmented to include subtypes of mind wandering and rumination. One hundred and seventy-eight participants sourced from professional networks (Mage = 53.13; SD = 11.80) completed an online questionnaire measuring dispositional mindfulness, metacognitive beliefs, rumination, mind wandering, worry, anxiety and depression. Effects of meditation frequency on these variables were examined, as were the relationships between them. Dispositional mindfulness was significantly negatively correlated with metacognitive beliefs, which were positively correlated with worry, mind wandering and rumination, all of which were positively correlated with symptomology. Significant correlations were stronger for spontaneous mind wandering and brooding rumination than their counterparts. Those reporting a daily meditation practice scored significantly higher on three of the five facets of mindfulness and significantly lower on anxiety and depression symptomology and several CAS elements than those who rarely meditated. Changes in metacognitive beliefs are a potential pathway for MBI-driven reductions in anxiety and depression symptomology. Increases in dispositional mindfulness through MBIs are likely to reduce metacognitive beliefs, which reduce maladaptive processes of the CAS, flowing on to reductions in symptomology. A daily meditation practice appears to increase the efficacy of this mechanism. Subtypes of mind wandering and rumination differ in their contribution to this pathway, perhaps more accurately represented as extremes on their respective continua rather than the current categorical model of typologies measured independently.